Collateral damage? Micro-simulation of transaction cost shocks on the value of central bank collateral - Rudolf Alvise Lennkh; Florian Walch (European Central Bank (ECB), 2015)
Transaction cost shocks in financial markets are known to affect asset prices. This paper analyses how changes in transaction costs may affect the value of assets that banks use to collateralise borrowings in monetary policy operations. Based on a simple asset pricing model and employing a dataset of hypothetical Eurosystem collateral positions, we simulate and quantify the resulting change in collateral value pledged by counterparties to the Eurosystem, resulting from a transaction cost shock. A 10 basis point increase in transaction costs entails a direct -0.30% decrease of collateral value and a -0.07% decrease when adjusted for the expected reduction in the number of trades of each asset. We conclude that banks will on average suffer small collateral losses while selected institutions could face a considerably larger collateral decrease.
Keywords: C15; E59; G12; 330; Central Bank; collateral; monetary policy; transaction cost